ENVIRONMENTAL, SOCIAL AND GOVERNANCE DISCLOSURES AND SHAREHOLDERS’ WEALTH MAXIMIZATION AMONG LISTED INDUSTRIAL GOODS COMPANIES IN NIGERIA (Journal of Global Accounting, 2024)
There is a global awareness that financial performance is not the only factor that influence shareholders’ wealth as other non-financial elements such as environmental, social and governance impacts are equally important when assessing the value of the firm. The main objective of this study was to ascertain the effect of environmental, social and governance (ESG) disclosures on shareholders’ wealth of listed industrial goods companies listed on the Nigerian Exchange Group from 2013 to 2023. Ex post facto research design was employed, secondary data were used and purposive sampling technique was adopted to select twelve industrial goods firms.  The method of data analysis employed was ordinary least square regression analysis and the statistical software used was E-views version 10. The result of the data analysis revealed that environmental performance disclosure and governance performance disclosure have significant positive effect while social performance disclosure has no significant effect on economic value added of listed industrial goods firms in Nigeria. Thus, the study concluded that ESG disclosures have significant effect on shareholders’ wealth of listed industrial goods companies in Nigeria. Based on the above findings, it was recommended that industrial goods companies should institute and disclose environmentally friendly policies since it portrays their commitment towards achieving the goal of sustainable development. It was also recommended that corporate governance mechanisms of the firms should be disclosed adequately in the annual report since it affects investors’ evaluation of firm’s capability to create wealth in future.
Keywords: Economic Value Added, Environmental Performance; Governance Performance; ESG; Shareholders Wealth